Chemical Examination of the Seeds of Trichosanthes anguina Linn - Yadav, R.N.; Syeda, Yasmeen (Asian Journal of Chemistry, 2010)
The present paper deals with the isolation and characterization of kaempferol, quercetin and kaempferol 3-O-β glucoside from the seeds of Trichosanthes anguina.